Calcium oxalate crystallization in synthetic urinary medium: the impact of resorcinares and calixarenes - Bottrill, Odin; Boon, Matthew; Jones, Franca; Mocerino, Mauro (RSC, 2022)
Kidney stones are an ailment that affects many people globally. While kidney stones can sometimes be treated with simple dietary changes this does not solve all cases. Most kidney stones are comprised predominantly of calcium oxalate and there are few very options in terms of accepted treatments for patients who suffer from this reoccurring condition. This research investigates the use of additives, resorcin[4]arenes and calix[4]arenes functionalised with three different amino acids (lysine, aspartic acid and proline) and their impact on the nucleation, morphology and zeta potential of calcium oxalate in a synthetic urine environment. The resorcin[4]arene functionalised with aspartic acid showed the stabilisation of calcium oxalate dihydrate rather than calcium oxalate monohydrate typically observed. The calix[4] arenes functionalised with proline and lysine showed large impacts on the morphology of the crystals formed. Additionally, the additives show significant impacts on the zeta potential of the crystals formed. It was also discovered that all three additives show evidence of incorporation to different extents through the crystal. These impacts were only observed when the macrocycles functionalised with amino acids were present, as the free amino acids showed minimal impact.